THE STATE OF RESEARCH OF THE NOTION AND THE SUBJECT OF AIR LAW OF UKRAINE - Шереметьєва, Є. Т.; Шереметьєва, О. Ю. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The article examines the meaning of the object and air law Ukraine.